The Influence of Logistics Cost Efficiency, Information Technology, and Service Quality on Supply Chain Performance in Indonesian Logistics Companies - Nia Aini; Muhammad Tohir (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The influence of Cost Efficiency in Logistics, Information Technology, and Service Quality Impact on Supply Chain Performance. is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to develop a hypothesis about the influence between variables that will be used in future research. The research objects are from online libraries such as Google Scholar, Mendeley, and other academic online platforms. The research method uses library research sourced from e-books and open access e-journals. The analysis used is descriptive qualitative. The results of this article: 1) Cost efficiency in logistics affects supply chain performance .; 2) Information technology affects supply chain performance.; and 3) Service quality affects supply chain performance.